Efektivitas Analisis Kebutuhan Ekonomi dan Sosial Komunitas Nelayan Miskin di Desa Paluh Sibaji Kecamatan Pantai Labu Kabupaten Deli Serdang - Bayu Rizky Ananda; Agus Suriadi; Randa Putra Kasea Sinaga (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Indonesia, as an archipelagic country, has vast potential in marine resources; however, the welfare of poor fishing communities remains far from satisfactory due to various economic and social limitations. This study aims to analyze the economic and social needs of poor fishermen who face challenges such as low income, limited access to education and healthcare, and dependence on middlemen. The research was conducted in Paluh Sibaji Village, Pantai Labu Subdistrict, Deli Serdang Regency. The key informant was the Head of Paluh Sibaji Village, with three poor fishermen serving as main informants and fishermen’s families as additional informants. Data collection was carried out through literature review and field studies, including observation, interviews, and documentation. The data obtained in the field were then qualitatively analyzed until conclusions could be drawn. Based on the findings, the living conditions of poor fishermen in Paluh Sibaji Village reveal ongoing multidimensional economic and social needs. Referring to Sukirno’s (2005) theory of economic needs, it is evident that low per capita income, limited employment opportunities, unequal income distribution, and inadequate economic infrastructure persist. An analysis based on Abraham Maslow’s (1943) theory of social needs indicates that poor fishermen in Paluh Sibaji experience a sense of belonging and social bonds, love and affection, as well as social interactions within the community, although these remain limited and not yet optimal.